1987
DOI: 10.1002/etc.5620060802
|View full text |Cite
|
Sign up to set email alerts
|

Environmental dechlorination of PCBs

Abstract: The polychlorinated biphenyls (PCBs) in sediment and/or fish samples from at least five different locations show changes in gas chromatographic (GC) peak distribution indicative of reductive dechlorination. Several different dechlorination processes, each presumably mediated by a different population of anaerobic bacteria with its own distinctive pattern of PCB congener selectivity, appear to be operating. Six of these processes have been characterized in detail as to the changes occurring in each of the 126 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(20 citation statements)
references
References 15 publications
(10 reference statements)
0
18
0
2
Order By: Relevance
“…Evidence for PCB reductive dechlorination processes via congener analysis was first reported in sediments from the upper Hudson River (Brown et al 1987). The chlorine distribution patterns of lower chlorinated congeners, which dominated the sediments, suggested that reductive dechlorination of chlorines in the meta - and para -positions was occurring (Quensen et al 1988;Quensen et al 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Evidence for PCB reductive dechlorination processes via congener analysis was first reported in sediments from the upper Hudson River (Brown et al 1987). The chlorine distribution patterns of lower chlorinated congeners, which dominated the sediments, suggested that reductive dechlorination of chlorines in the meta - and para -positions was occurring (Quensen et al 1988;Quensen et al 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Over the last few years, several Dhc strains with various dechlorinating capabilities have been isolated (i.e., Dhc strains 195, VS, GT, H10, BAV1, CBDB1, JNA) (Sung et al 2006;Copeland et al 2007a, b;He et al 2005;Kube et al 2005;Adrian et al 2009;Loeffler et al 2013;Laroe et al 2014;Kube et al 2005;Bedard et al 2007;Pieper and Seeger 2008;Laroe et al 2014;Fricker et al 2014). Moreover, PCB biodegradation has been also attributed to Dhc strains CDBD1 and 195, the activity of which has been reported in environmental matrices or microcosm studies (Brown et al 1987;Bedard et al 2005;Wiegel and Wu 2000). JNA is the only Dhc strain reported to be able to mediate the anaerobic degradation of hexa-CBs and hepta-CBs by process N into byproducts, which can be aerobically degraded into di-and tri-CBs by processes LP or Q (Bedard 2003;Bedard and Quensen 1995;Pieper 2005;Field and Sierra-Alvarez 2008;Laroe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These compounds can be degraded by microbial communities naturally present in the environment through the combination of two processes: anaerobic reductive dechlorination (organohalide respiration) of higher chlorinated congeners and aerobic oxidative degradation of lower chlorinated congeners. 3 Natural attenuation of PCBs by reductive dechlorination is observed in the environment, 47 but the process is slow and factors affecting rates are not well understood. Since many commercial PCB mixtures such as Aroclors are highly chlorinated, microbial reductive dechlorination is often a rate-limiting step for PCB degradation in the environment.…”
Section: Introductionmentioning
confidence: 99%